2021
DOI: 10.3390/ani11041030
|View full text |Cite
|
Sign up to set email alerts
|

Is Hay for the Birds? Investigating Landowner Willingness to Time Hay Harvests for Grassland Bird Conservation

Abstract: Birds in agricultural environments have exhibited steep global population declines in recent decades, and effective conservation strategies targeting their populations are urgently needed. In grasslands used for hay production, breeding birds’ nest success improves substantially if hay harvests are delayed until after mid-July. However, few studies have investigated private hay producers’ willingness to alter their harvesting practices, which is a critical factor for bird conservation where most land is privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Managing grasslands to avoid overgrazing in general and disturbance to nesting and juvenile birds in particular, whether from grazing by bison or cattle, hay harvesting, or patch burning, makes a critical difference for Bobolinks and other ground-nesting birds [ 22 , 40 ]. Our findings show that both Bobolink abundance and productivity significantly increased following the departure of grazing animals ( Figure 4 and Figure 5 ), while both Bobolink abundance and productivity exhibited significant declines when cattle grazing was replaced with bison grazing in our study area ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Managing grasslands to avoid overgrazing in general and disturbance to nesting and juvenile birds in particular, whether from grazing by bison or cattle, hay harvesting, or patch burning, makes a critical difference for Bobolinks and other ground-nesting birds [ 22 , 40 ]. Our findings show that both Bobolink abundance and productivity significantly increased following the departure of grazing animals ( Figure 4 and Figure 5 ), while both Bobolink abundance and productivity exhibited significant declines when cattle grazing was replaced with bison grazing in our study area ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the relative lack of protection for grasslands, most of which are privately owned [ 21 , 22 ], reintroducing bison may bring more attention and support for grassland conservation, benefiting grassland birds. Public interest and funding for popular species have been leveraged to meet multiple conservation objectives in other cases, such as Northern Bobwhites ( Colinus virginianus ) acting as an umbrella species for some other species of grassland and shrubland birds [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hay fields may provide important habitat for a handful of species. However, haying can lead to declining bird abundance (Bollinger et al 1990), though Gruntorad et al (2021) found that most farmers were willing to delay haying in order to benefit birds. Unlike corn and soy fields, hay fields were most preferred by several bird species (Supporting information).…”
Section: Discussionmentioning
confidence: 99%
“…2023;115:3035-3044. wileyonlinelibrary.com/journal/agj2 3035 within the larger ecosystem (Vinton & Larsen, 2022;Whitcomb, 1989). The primary use of Sandhills subirrigated meadows is hay production, which provides a major source of winter feed for cattle operations (Coady & Clark, 1993;Gruntorad et al, 2021;Volesky et al, 2011). Haying on meadows typically occurs from late-June to August.…”
Section: Introductionmentioning
confidence: 99%
“…The primary use of Sandhills subirrigated meadows is hay production, which provides a major source of winter feed for cattle operations (Coady & Clark, 1993; Gruntorad et al., 2021; Volesky et al., 2011). Haying on meadows typically occurs from late‐June to August.…”
Section: Introductionmentioning
confidence: 99%